Safe use of the ketogenic diet in an infant with microcephaly, epilepsy, and diabetes syndrome: a case report - Walter A. Zegarra; William B. Gallentine; Maura R. Ruzhnikov; Catherine A. McAndrews; Anna L. Gloyn; Ananta Addala (BMC, 2023)
Abstract Background Microcephaly, epilepsy, and diabetes syndrome (MEDS) is a rare syndromic form of monogenic diabetes caused by bi-allelic loss of function mutations in IER3IP1. In vitro studies have shown that loss of IER31P leads to apoptosis in both neurons and pancreatic β-cells. Simultaneous management of seizures and diabetes is challenging in patients with MEDS. We present the challenges and successes in the use of ketogenic diet in an infant with insulinopenic diabetes. Case presentation Our term female proband presented at 2 months of age with new onset multifocal seizures followed by the onset of infantile spasms (IS) at 4 months of age. An epilepsy gene panel identified bi-allelic variants, c.239T > G (p.Leu80*) and c.2T > A (initiator codon), in IER3IP1 that were subsequently shown to be inherited in trans. Following initiation of steroid therapy for IS, the patient developed clinically apparent insulin requiring diabetes. Her epilepsy was ultimately refractory to multiple antiseizure medications, thus the ketogenic diet (KD) was initiated. We were able to successfully titrate to a therapeutic KD ratio of 3:1 and maintain a ketotic state without diabetic ketoacidosis (DKA). With intercurrent illnesses, however, the patient had rapid decompensation and mild DKA due to delays in treatment, and for this reason, KD was discontinued after 5 months. Conclusions We report two novel IER31P1 mutations in a patient with MEDS and the successful management of the cooccurring conditions of IS and insulinopenic diabetes with the KD. Our experience underscores the importance of careful monitoring during KD as our patient had DKA more easily when on the KD.